Social amoebae: environmental factors influencing their distribution and diversity across south-western Europe. (Microbial ecology, 2011)
The social amoebae (dictyostelids) are the only truly multicellular lineage within the superkingdom Amoebozoa, the sister group to Ophistokonts (Metazoa+Fungi). Despite the exceptional phylogenetic and evolutionary value of this taxon, the environmental factors that determine their distribution and diversity are largely unknown. We have applied statistical modeling to a set of data obtained from an extensive and detailed survey in the south-western of Europe (The Iberian Peninsula including Spain and Portugal) in order to estimate some of the main environmental factors influencing the distribution and diversity of dictyostelid in temperate climates. It is the first time that this methodology is applied to the study of this unique group of soil microorganisms. Our results show that a combination of climatic (temperature, water availability), physical (pH) and vegetation (species richness) factors favor dictyostelid species richness. In the Iberian Peninsula, dictyostelid diversity is highest in colder and wet environments, indicating that this group has likely diversified in relatively cold places with high levels of water availability.

Dictyostelids from Mediterranean forests of the south of Europe - Romeralo, María; Lado, Carlos (Mycological Progress, 2006)
The first results of a study of dictyostelid diversity in soils of Mediterranean vegetation are presented. Surface soil samples were collected during 2003–2004 from different Mediterranean forests in Spain and Portugal and were plated out for cellular slime moulds. Isolated during this study were 14 species of dictyostelids. One species, Dictyostelium firmibasis is reported for the first time from Europe, and nine (Dictyostelium aureo-stipes, Dictyostelium sp. 1, Dictyostelium fasciculatum, Dictyostelium giganteum, Dictyostelium implicatum, Dictyostelium leptosomum, Dictyostelium sphaerocephalum, Polysphondylium candidum, Polysphondylium pallidum) are new records for the Mediterranean region. Members of the three genera Dictyostelium (ten species), Polysphondylium (three species) and Acytostelium (one species) are present in this region of the world. Comments on their diversity and distribution are included.
Keywords: Dictyostelids; distribution (PG); diversity; mediterranean forest soils

Dictyostelids from Mediterranean forests of the south of Europe (Mycological Progress, 2006)
The first results of a study of dictyostelid diversity in soils of Mediterranean vegetation are presented. Surface soil samples were collected during 2003–2004 from different Mediterranean forests in Spain and Portugal and were plated out for cellular slime moulds. Isolated during this study were 14 species of dictyostelids. One species, Dictyostelium firmibasis is reported for the first time from Europe, and nine (Dictyostelium aureo-stipes, Dictyostelium sp. 1, Dictyostelium fasciculatum, Dictyostelium giganteum, Dictyostelium implicatum, Dictyostelium leptosomum, Dictyostelium sphaerocephalum, Polysphondylium candidum, Polysphondylium pallidum) are new records for the Mediterranean region. Members of the three genera Dictyostelium (ten species), Polysphondylium (three species) and Acytostelium (one species) are present in this region of the world. Comments on their diversity and distribution are included.